Cleavage efficient 2A peptides for high level monoclonal antibody expression in CHO cells - Chng, Jake (2016)
Linking the heavy chain (HC) and light chain (LC) genes required for monoclonal antibodies (mAb) production on a single cassette using 2A peptides allows control of LC and HC ratio and reduces non-expressing cells. Four 2A peptides derived from the foot-and-mouth disease virus (F2A), equine rhinitis A virus (E2A), porcine teschovirus-1 (P2A) and Thosea asigna virus (T2A), respectively, were compared for expression of 3 biosimilar IgG1 mAbs in Chinese hamster ovary (CHO) cell lines. HC and LC were linked by different 2A peptides both in the absence and presence of GSG linkers. Insertion of a furin recognition site upstream of 2A allowed removal of 2A residues that would otherwise be attached to the HC. Different 2A peptides exhibited different cleavage efficiencies that correlated to the mAb expression level. The relative cleavage efficiency of each 2A peptide remains similar for expression of different IgG1 mAbs in different CHO cells. While complete cleavage was not observed for any of the 2A peptides, GSG linkers did enhance the cleavage efficiency and thus the mAb expression level. T2A with the GSG linker (GT2A) exhibited the highest cleavage efficiency and mAb expression level. Stably amplified CHO DG44 pools generated using GT2A had titers 357, 416 and 600 mg/L for the 3 mAbs in shake flask batch cultures. Incomplete cleavage likely resulted in incorrectly processed mAb species and aggregates, which were removed with a chromatin-directed clarification method and protein A purification. The vector and methods presented provide an easy process beneficial for both mAb development and manufacturing.